Growth in the Aftermath of Psychosis: Characterizing Post-traumatic Growth in Persons With First Episode Psychosis in Singapore - Lee, Ying Ying; Seet, Vanessa; Chua, Yi Chian; Verma, Swapna Kamal; Subramaniam, Mythily (Frontiers in Psychiatry, 2022)
Experiencing first episode psychosis (FEP) is a highly traumatic life event. However, there is evidence to show that the outcome of psychosis is more nuanced than was conventionally thought. Young persons with FEP can grow from the experience of psychosis. In this study, we aim to characterize post-traumatic growth (PTG) in persons with FEP over one year. A total of 99 FEP clients receiving services from an early psychosis intervention team in Singapore were recruited. The PTG Inventory, among other scales, like Questionnaire on the Process of Recovery and Connor-Davidson Resilience Scale, were administered in this population. A total of 52 participants completed the questionnaire at two timepoints (one year apart). The Reliable Change Index was calculated for participants who completed both timepoints. Repeated measures of correlation were performed, which identified personal recovery and resilience to be associated with PTG in this sample. This clinical population exhibited PTG in the aftermath of psychosis. PTG was associated with personal recovery and resilience, but not clinical indicators, like symptoms and functioning. Data from this study suggests that recovery and growth from first episode psychosis is a possibility. Clinical implications, strengths and limitations of this study were discussed.